The Effect of Training, Job Stress, and Motivation on Work Productivity with Unsafe Actions as An Intervening Variable - Putra, Gilang Andhika; Badruzaman, Jajang; Supriadi, Apip (SMART Insight, 2024)
This research aims to test the direct and indirect influence between training, work stress, and motivation on work productivity with unsafe actions as an intervening variable. The study was conducted on employees of a Steam Power Plant contractor in Cirebon Regency. Sampling was carried out using a proportional start-up random sampling technique, with a total sample size of 152 samples, who were active employees at PT Cipta Anugrah Sejahtera and PT Star Plus. The research instrument used was a questionnaire with a Likert scale. The analysis technique used is path analysis using the SPSS version 27 application. The results of this study show that 1) Job stress, motivation and productivity variables are in the good category, while training and unsafe actions very good category. 2) Training has a negative and significant effect on unsafe actions. 3) Work stress has a positive and significant effect on unsafe actions. 4) Motivation has a negative and insignificant effect on unsafe actions. 4) Training, work stress and motivation simultaneously have a significant effect on unsafe acts. 5) Training, work stress, motivation and unsafe actions simultaneously has a significant effect on work productivity.